PENERAPAN KONSEP ARSITEKTUR PERILAKUPADA PANTI WERDHA DI TAMAN MALIBU MEDAN - Fauzan Fauzan; Nusa Ekasyah Putra; Melly Adriana (Jurnal Arsitektur ARCADE, 2023)
Abstract: The elderly are the last phase in a person's life cycle, where physical and mental changes become more pronounced, thus requiring special attention to improve their well-being. However, with the advancement of time and increasingly busy lives, families tend to pay less attention and care for elderly parents. Changes in the family structure make them realize that the presence of the elderly in the family can be a burden. In designing a solution to this problem, the analytical method is used by conducting field observations, face-to-face interviews, and direct interaction with the elderly to thoroughly understand the problems they face. In designing the residence, the concept created aims to support the activities of elderly residents. In addition, the concept of behavioral architecture is used to create a comfortable environment and have a positive impact on the nursing home. The importance of physical comfort in buildings also has a positive psychological effect on elderly residents. However, in designing a retirement home specifically for the elderly, it is important to understand their characteristics and needs. The management of degenerative diseases is of particular concern, especially in behavioral architecture principles that concern safety and comfort. However, many nursing homes currently face obstacles in performing their functions well. Therefore, it is also necessary to pay attention to facilities that can support the psychological aspects of the elderly.Keyword: elderly, retirement home, behaviroal architectureAbstrak: Lansia adalah fase terakhir dalam siklus kehidupan seseorang, di mana perubahan fisik dan mental menjadi lebih nyata, sehingga perlu perhatian khusus untuk meningkatkan kesejahteraan mereka. Namun, dengan kemajuan zaman dan kehidupan yang semakin sibuk, keluarga cenderung kurang memperhatikan dan merawat orang tua lanjut usia. Perubahan dalam struktur keluarga membuat mereka menyadari bahwa kehadiran lansia dalam keluarga bisa menjadi beban. Dalam merancang solusi untuk masalah ini, metode analitik digunakan dengan melakukan observasi lapangan, wawancara tatap muka, dan interaksi langsung dengan lansia untuk memahami masalah yang mereka hadapi secara menyeluruh. Dalam perancangan hunian, konsep yang diciptakan bertujuan untuk mendukung aktivitas penghuni lansia. Selain itu, konsep arsitektur perilaku digunakan untuk menciptakan lingkungan yang nyaman dan berdampak positif bagi panti werdha. Pentingnya kenyamanan fisik dalam bangunan juga memiliki efek psikologis yang positif bagi penghuni lansia. Namun, dalam merancang panti werdha khusus untuk lansia, penting untuk memahami karakteristik dan kebutuhan mereka. Penanganan penyakit degeneratif menjadi perhatian khusus, terutama dalam prinsip arsitektur perilaku yang menyangkut keamanan dan kenyamanan. Namun, banyak panti werdha saat ini menghadapi kendala dalam menjalankan fungsinya dengan baik. Oleh karena itu, perlu diperhatikan juga fasilitas yang dapat mendukung aspek psikologis lansia.Kata Kunci: lansia, panti werdha, arsitektur perilaku